Association between prescribed enteral diet and infused versus and clinical outcome in elderly stays in an Intensive Care Unitasociación entre dieta enteral (Research, Society and Development, 2021)
Introduction: The elderly public is at greater risk of developing nutritional deficits, since there is an impairment of physiological function. Objective: to evaluate the association between the prescribed versus infused enteral diet and the clinical outcome of elderly patients admitted to an Intensive Care Unit. Methodology: The study was sectional, developed with elderly in Intensive Care Unit of the Hospital Universitário Lauro Wanderley da Paraíba, where they were evaluated through a nutritional monitoring form. Statistical analysis used Chi-square tests assuming a significance level (p